1951
DOI: 10.1021/ja01145a084
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of Conjugated Fatty Acids. I. Alkali-isomerized Linoleic Acid

Abstract: Rearrangement of 1-4 double bonds of diand polyolefinic compounds to the conjugated position has been shown to occur during treatment with catalysts such as nickel2'3 or alkali4'6 at high temperatures, and during autoxidation.6'7 Evidence for this change has been based to a considerable extent on spectroscopic data. Relatively little is known

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

1955
1955
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…In 1963, Riel (28) noted that summer milk fat had more conjugated dienoic acid than winter milk fat. More recently, conjugated linoleic acid (CLA) has been shown to inhibit chemically induced tumors (1, 10, 17), prevent atherosclerosis (24), and improve the protein-to-fat ratio in experimental animals (8).CLAs can be produced by alkaline isomerization, but there are as many as 16 isomers which are not fully characterized (26,29). Ruminant nutritionists have attempted to increase the naturally occurring CLA content of cow's milk via diet changes and alterations of ruminal fermentation (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1963, Riel (28) noted that summer milk fat had more conjugated dienoic acid than winter milk fat. More recently, conjugated linoleic acid (CLA) has been shown to inhibit chemically induced tumors (1, 10, 17), prevent atherosclerosis (24), and improve the protein-to-fat ratio in experimental animals (8).CLAs can be produced by alkaline isomerization, but there are as many as 16 isomers which are not fully characterized (26,29). Ruminant nutritionists have attempted to increase the naturally occurring CLA content of cow's milk via diet changes and alterations of ruminal fermentation (9).…”
mentioning
confidence: 99%
“…CLAs can be produced by alkaline isomerization, but there are as many as 16 isomers which are not fully characterized (26,29). Ruminant nutritionists have attempted to increase the naturally occurring CLA content of cow's milk via diet changes and alterations of ruminal fermentation (9).…”
mentioning
confidence: 99%
“…As many as 16 CLA isomers are known to be produced by alkaline isomerization of linoleic acid (LA) [27,33]. Of the CLA isomers, the cis-9, trans-11 (c9, t11) and the t10, c12 configurations are considered to be the most effective [31].…”
mentioning
confidence: 99%
“…The rearrangement was shown to occur during auto oxidation of poyolefins (Bolland and Koch, 1945;Farmer et al, 1943) and treatment in the presence of nickel catalyst (Bailey, 1945;Radlove et al, 1946) or in the presnce of alkali at high temperatures ( Moore, 1939;Kass and Burr;1939). Nichols and his co-workers (Nichols et al, 1951) showed that the isomerisation of linoleic acid to CLAs could be achieved by alkali isomerisation at high temperatures. Furthermore, with available literature and analytical methodology, UV spectrometry, they were able to show that the predominant products in the alkali isomerisation were 9c11t and 10t12c CLAs.…”
Section: Introductionmentioning
confidence: 99%
“…With sophisticated analytical techniques, several reseachers have confirmed the fact that the main products formed in the alkali isomerization of 9c12c fatty acid were indeed 9c11t and 10t12c. Nichols and his co-workers (Nichols et al, 1951) have also used theoretical considerations and predicted the formation of conjugated linoleic acids from the cis/trans isomers of methylene interrupted 9,12 linoleic acids.…”
Section: Introductionmentioning
confidence: 99%